Hybrid organic-inorganic polyoxometalates : synthesis and characterisation of organoarsonate and organophosphonate functionalised polyoxovanadate clusters - Breen, John Michael (Trinity College (Dublin, Ireland). School of Chemistry, 2010)
This thesis presents a significant contribution of research to the field of hybrid inorganic- organic polyoxometalates. Herein the functionalisation of polyoxovanadate clusters with aryl arsonates and aryl phosphonates is described and the structural and physiochemical properties of the product materials are discussed. Chapter 1 introduces the reader to the field of research, highlights recent significant achievements and puts accomplishments into a broader context.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin